2014
DOI: 10.7314/apjcp.2014.15.17.7395
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutant of Human Papillomavirus Type 18 E6E7 Fusion Gene and its Transforming Activity

Abstract: Background: Persistent human papillomavirus (HPV) infection, especially with high-risk types such as HPV16 and HPV18, has been identified as the primary cause of cervical cancer. E6 and E7 are the major onco-proteins of high-risk HPVs, which are consistently expressed in HPV infected tissues but absent in normal tissues and represent ideal therapeutic targets for immunotherapy of cervical cancer. Materials and Methods: In this study, the optimized fusion gene HPV18 E6E7 (HPV18 ofE6E7) was constructed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The stop codon is removed from E7 to permit fusion with HPV18 E7. A parallel set of inactivating mutations have also been introduced into HPV18 E7 (detox), specifically, C27G (62), E29G (16), and C98G (63), and the stop codon was removed from HPV18 E7 to permit fusion with HPV16 E6. The HPV16 E6(detox) gene contains multiple mutations to disrupt oncogenic activity by targeting key cysteine residues in the two zinc finger domains via C63G and C106G mutations.…”
Section: Methodsmentioning
confidence: 99%
“…The stop codon is removed from E7 to permit fusion with HPV18 E7. A parallel set of inactivating mutations have also been introduced into HPV18 E7 (detox), specifically, C27G (62), E29G (16), and C98G (63), and the stop codon was removed from HPV18 E7 to permit fusion with HPV16 E6. The HPV16 E6(detox) gene contains multiple mutations to disrupt oncogenic activity by targeting key cysteine residues in the two zinc finger domains via C63G and C106G mutations.…”
Section: Methodsmentioning
confidence: 99%
“…E6 and E7 are the major oncoproteins of high-risk HPVs (Nakagawa et al, 1995;Zhou et al, 2014). Since E6 and E7 are consistently expressed in most cervical cancers and their precursor lesions but do not exist in normal tissues, these oncoproteins are targets for therapeutic vaccines that are presently in development, administering E6/E7 either in live vectors, as peptides, protein or nucleic acid form, or in cell-based vaccines (Seo et al, 2009;Yan et al, 2009;Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the works of our laboratory and other international laboratories have shown that HPV is also an important cause of esophageal cancer (4)(5)(6)(7)(8)(9)(10)(11)(12). More than 80% of esophageal cancer patients in China's Shantou area are concomitant with HPV 16 and 18 infections.…”
Section: Original Articlementioning
confidence: 99%